2018
DOI: 10.1007/s12070-018-1520-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Perception of Self-Efficacy and Involvement in Young Children with Prelingual Hearing Loss

Abstract: Appropriate intervention needs to support families and consider them as a part of rehabilitation program. Parents who have high self-efficacy are more likely to put their knowledge and skills into action and have positive interactions with their children. In addition, there has been a positive relation between parental involvement and child educational success. The aim of present study was evaluating maternal perception of both self-efficacy and involvement between mothers of children with hearing aid and coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
1
0
4
Order By: Relevance
“…Finally, the current study revealed that, there were highly statistical positive correlation between the studied parents' total level of knowledge, total reported practices and their total self-competence level at pre, post and after 3 months of empowerment program implementation. These findings were matched with study done by Joulaie et al, (2019) entitled " Maternal Perception of Self-Efficacy and Involvement in Young Children with Prelingual Hearing Loss" and explained that, Parents who have high self-efficacy are more likely to put their knowledge and skills into action and have positive interactions with their children. .…”
Section: Discussionmentioning
confidence: 67%
“…Finally, the current study revealed that, there were highly statistical positive correlation between the studied parents' total level of knowledge, total reported practices and their total self-competence level at pre, post and after 3 months of empowerment program implementation. These findings were matched with study done by Joulaie et al, (2019) entitled " Maternal Perception of Self-Efficacy and Involvement in Young Children with Prelingual Hearing Loss" and explained that, Parents who have high self-efficacy are more likely to put their knowledge and skills into action and have positive interactions with their children. .…”
Section: Discussionmentioning
confidence: 67%
“…[3][4][5] Normal gelişim gösteren çocukların algı ve becerilerinin gelişmesinde son derece etkiye sahip olan ebeveynlik, işitme kaybı gibi çocuğu hemen hemen bütün gelişim alanlarında yetersiz hissettiren bir durum karşısında çok daha önemli olmaktadır. 6 İşitme kayıplı çocuğa sahip ebeveynlerin, bu durum karşısında artan sorumlulukları ve uzun vadeli zorluklarla karşılaşmaları stresli bir durum oluşturmaktadır. 7 Ebeveynlik öz yeterliği, bir ebeveynin çocuğunu yetiştirmeyle ilgili görevleri ve durumları ne kadar etkili bir şekilde yönetebileceğine ilişkin inancı veya ebeveyn olarak yetkin ve etkili bir şekilde performans gösterebilme derecesi olarak tanımlanabilir.…”
Section: Discussionunclassified
“…Ancak ebeveyn öz yeterliği ile ebeveynin çocukla etkileşimi, çocuğu yetiştirmesi, çocuğun akademik başarısına etkisi, çocuğu tanıması, geliştirmesi gibi çocuk eğitim yeterliği ile ilişkilendirilebilen çalışmaların var olduğu görülmüştür. 6,9,21 Bu çalışmalarda da çalışmamızı destekler nitelikte ebeveyn öz yeterliği ile bahsi geçen maddeler arasında pozitif yönde ilişkiler gözlenmiştir. Benzer şekilde yapılan başka bir çalışmada, ebeveyn öz yeterliği ile ebeveynin çocuklarının gelişimine katkısı arasında pozitif bir ilişki olduğu, çocuklarının öğrenme sürecine katılan ebeveynlerin öz yeterliklerinin güçlendiği tespit edilmiştir.…”
Section: Discussionunclassified
See 2 more Smart Citations